Sketch book for the artist - Simblet, Sarah
Covering a wide range of themes from portraits to plant studies and still life and showing how to tackle each subject in a variety of different ways, the "Sketch Book for the Artist aims to widen the reader's understanding of drawing and to inspire them to pick up a pencil and draw. Alongside drawings by famous artists, the book uses the author's own sketch book as a way to examine attitudes and demonstrate specific techniques.